The Synthesis of Quinidine Salicylate Ester Compound - Intan Nurjaya; Muhammad Hanafi; Puspa D.N Lotulung; Teni Ernawati; Sri Mursiti (Jurnal Kimia Terapan Indonesia, 2018)
Quinidine a compound isolated from quinine plants, one of the species of quinine plants is (Chincona ledgereriana) From PT SIL Lembang. The purpose of this study was obtain quinidine salicylate ester through esterification reaction. In this study, the synthesis of quinidine ester compound by esterification reaction was conducted. Esterification reaction was conducted by using DCC activator and DMAP catalyst with one carboxylic acid namely salicylate acid producing new compound namely quinidine salicylate, Subsequent Quinidine salicylate was obtained in the form of oil with 97% yield. The compound obtained from the synthesis was then identified using Thin Layer Chromatography continue analyzed using with Spectrophotometer, LC-ESI-MS spectroscopy. Results show that the target compound has been successfully synthesized.